The cytoprotective effects of verapamil and iloprost (ZK 36374) on ischemia/reperfusion injury of kidneys - (:unkn) unknown (Springer-Verlag, 1993)
We investigated the cytoprotective effects of verapamil, a Ca channel blocker, and of iloprost (ZK 36374), a stable prostacyclin analogue, on ischemia/reperfusion (I/R) injury in Wistar albino rat kidneys that were subjected to 60 min of warm ischemia and reperfusion. The groups included sham, ischemia-untreated (ISCH), verapamil-treated (VER), iloprost-treated (ILO), and verapamil + iloprost (VER+ILO)-treated rats. The 7-day survival of all the treated groups was better than that of the ISCH group. The creatinine concentration on the 3rd day was significantly lower in the VER+ILO group than in the ISCH group. Serum creatinine on day 3 was also low in the VER+ILO groups compared to the ISCH group, although the differences were not significant. The creatinine values on day 7 were significantly lower in the VER and ILO group than in the control, VER, or ILO groups. The malondialdehyde (MDA) concentrations of the kidney cortex tissue after reperfusion in all groups were higher than normal. The tissue-reduced glutathione (GSH) concentrations of the kidneys sampled immediately after reperfusion were significantly lower in the ISCH group than in all of the other treated groups. These results indicate that although verapamil and iloprost have independent cytoprotective effects on 60-min warm ischemia/reperfusion injury of rat kidneys, the protection afforded when both drugs are combined is synergistic. The mechanism of cytoprotection is not limited to the suppression of lipid peroxidation, and a nearly complete protection of reperfusion injury can be obtained by such an intervention. © 1993 Springer-Verlag.
Keywords: Iloprost, rat, kidney reperfusion; Preservation, reperfusion; Rat, kidney reperfusion; Reperfusion kidney, rat; Verapamil, rat, kidney reperfusion